2021
DOI: 10.1111/cts.13045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5‐HT receptor antagonists on cisplatin‐induced kidney injury

Abstract: Nausea, vomiting, and renal injury are the common adverse effects associated with cisplatin.Cisplatin is excreted via the multidrug and toxin release (MATE) transporter, and the involvement of the MATE transporter in cisplatin-induced kidney injury has been reported. The MATE transporter is also involved in the excretion of ondansetron, but the effects of 5-HT 3 receptor antagonists used clinically for cisplatin-induced renal injury have not been elucidated. Therefore, the aim of this study was to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…CDDP is mainly transported to renal tissues via organic cation transporter 2 (OCT2) at the renal basolateral membrane [ 12 , 13 ], whereas CDDP is excreted into urine through multidrug and toxin extrusion protein transporter 1 (MATE1), which is localized on the apical membrane [ 14 ], indicating that OCT2 and MATE1 should be responsible for CDDP-induced nephrotoxicity. As shown in a previous study using the mice model of CDDP-induced nephrotoxicity [ 8 ], the concomitant use of a first-generation 5-HT 3 RA (ondansetron, granisetron, or ramosetron) significantly increased CDDP accumulation in the kidneys and worsened renal damage. Conversely, the concomitant use of palonosetron had no effect on renal function compared with the use of CDDP alone.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…CDDP is mainly transported to renal tissues via organic cation transporter 2 (OCT2) at the renal basolateral membrane [ 12 , 13 ], whereas CDDP is excreted into urine through multidrug and toxin extrusion protein transporter 1 (MATE1), which is localized on the apical membrane [ 14 ], indicating that OCT2 and MATE1 should be responsible for CDDP-induced nephrotoxicity. As shown in a previous study using the mice model of CDDP-induced nephrotoxicity [ 8 ], the concomitant use of a first-generation 5-HT 3 RA (ondansetron, granisetron, or ramosetron) significantly increased CDDP accumulation in the kidneys and worsened renal damage. Conversely, the concomitant use of palonosetron had no effect on renal function compared with the use of CDDP alone.…”
Section: Discussionmentioning
confidence: 75%
“…Conversely, the concomitant use of palonosetron had no effect on renal function compared with the use of CDDP alone. An uptake study in hMATE1-expressing HEK293 cells revealed that the first-generation 5-HT 3 RAs have a lower IC 50 than palonosetron, thus, palonosetron is thought to have weaker MATE1 inhibitory activity than the first-generation 5-HT 3 RAs [ 8 ]. Furthermore, palonosetron was reported to interfere with OCT2 activity [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first approach, similar to the first approach, is for cisplatin renal injury ( Goda et al, 2021 ). Cisplatin is excreted via the multidrug and toxin release (MATE) transporter, and a 5-HT3 receptor antagonist is used as an antiemetic.…”
Section: Example Of Actual Research: Approach To Drug-induced Adverse Eventmentioning
confidence: 99%